Раскопки курганов у с. Новосельское Черноморского района Крыма - Анохин, В.В.; Кутайсов, В.А. (Археологический альманах, 2012)
В июле 1993 г. Западно-Крымская экспедиция КФ ИА НАНУ наряду с другими работами осуществила охранные раскопки трех курганов к северо-востоку от с. Новосельское [Анохин, 2004, 21 – 25] или в 2,0 – 2,5 км к юго-востоку от Калос Лимена. In July, 1993 guard excavations of three burial mounds were conducted to north-east of v. Novosel’skoe or in a 2,0 – 2,5 km south-east of Kalos Limen. Embankments were located on undergoing many years to the deep ploughing the field and predatory dig is damaged. Burial mounds were disposed in a row from a north-west on a southeast. These objects are marked on map 1899 and map 1957. Three burial mounds were investigational. Two from them contain burials of IV c. B.C. and base under a stone sculpture, in one it was investigational related to the middle stage of cultural and historical community of multiroller culture and dated the first half of II thousand B.C. Presently, on the basis of analysis of cartographic material about 5000 burial mounds are selected. Now after the excavations of the burial mound group described higher conducted by us them remained on three less than.